International Relations in the Perspective of Fiqh al-Siyasah - Abdillah, Masykuri; Masyrofah, Masyrofah (Jurnal Cita Hukum, 2024)
This article analyses the concept and practice of international relations according to fiqh al-siyasah, which is related to war and peace, international law, diplomacy, and international cooperation. This study emphasises the normative concept of international relations (al-‘alâqât al-dauliyyah) using international relations studies and international law. Thus, the sources of data or information in this study are the Quran, Hadis, the opinions of Muslim scholars (ulama) and theories of international relations and international law. Since the beginning, Islam has provided guidelines on relations between groups and kingdoms, which in today's context refer to international relations. In addition to the principles of international relations, the Quran and Hadith also provide normative references, which the Muslim scholars formulated as international law. Philosophically, there is a difference between secular international law and Islamic law derived from revelation understood by contextual ijtihad. However, at present, the majority of Muslim scholars believe that, in general, there is compatibility between the principles of modern international law and the principles of Islamic law, especially in the form of agreements ('uhûd and mawâtsiq), customs ('âdât), and ratio ('aql), which also recognised by Islamic law.